KINETICS OF CO OXIDATION ON CU-CO-FE OXIDE CATALYSTS SUPPORTED ON CARBON NANOTUBES: UDC 541.1+541.128 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2013)
Kinetics of CO oxidation on Cu-Co-Fe oxide catalysts supported on carbon nanotubes is investigated and it is shown, that the kinetic experimental data are submitted to the Eley-Readil mechanism in good agreement with bulk Cu-Co-Fe oxide catalysts. The data of activation energy for CO oxidation was determined for this catalyst.
Keywords: catalyst, carbon monoxide, kinetics, carbon nanotubes, oxide Cu-Co-Fe system